2021
DOI: 10.1242/dev.198846
|View full text |Cite
|
Sign up to set email alerts
|

WNT signaling in pre-granulosa cells is required for ovarian folliculogenesis and female fertility

Abstract: In mammalian ovaries, immature oocytes are reserved in primordial follicles until their activation for potential ovulation. Precise control of primordial follicle activation (PFA) is essential for reproduction, but how this is achieved is unclear. Here, we show that canonical wingless-type MMTV integration site family (WNT) signaling is pivotal for pre-granulosa cell (pre-GC) activation during PFA. We identified several WNT ligands expressed in pre-GCs that act in an autocrine manner. Inhibition of WNT secreti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 76 publications
(98 reference statements)
3
31
0
Order By: Relevance
“…Indeed, genes such as ctcf ( Wan et al, 2008 ), eIf4g ( Keiper 2019 ), alk4 ( Souquet et al, 2012 ), and hira ( Nashun et al, 2015 ; Burkhart et al, 2020 ) have all been shown to play essential roles in oocyte development and are maternally deposited. All other genes associated with this functional term are maternally deposited according to ZFIN expression data and include components of signaling pathways that pattern the early embryo such as Nodal and Wnt/β-cat ( Whitman 2001 ; Souquet et al, 2012 ; Fuentes et al, 2020 ; Habara et al, 2021 ) ( Supplementary Data sheet S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, genes such as ctcf ( Wan et al, 2008 ), eIf4g ( Keiper 2019 ), alk4 ( Souquet et al, 2012 ), and hira ( Nashun et al, 2015 ; Burkhart et al, 2020 ) have all been shown to play essential roles in oocyte development and are maternally deposited. All other genes associated with this functional term are maternally deposited according to ZFIN expression data and include components of signaling pathways that pattern the early embryo such as Nodal and Wnt/β-cat ( Whitman 2001 ; Souquet et al, 2012 ; Fuentes et al, 2020 ; Habara et al, 2021 ) ( Supplementary Data sheet S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several of these targets have been characterized in follicle activation. For example, studies have identified the importance of WNT signaling in pre-granulosa to granulosa cell differentiation ( Ford et al 2021 , Habara et al 2021 ). Further, TGFB1 signaling mediates cell cycle arrest in pre-granulosa cells ( Hardy et al 2018 , Granados-Aparici et al 2019 ), and inhibiting TGFB1 signaling promotes follicle activation ( Wang et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the luteal phase (LL vs. LH), the host genes of chi_circ_0000475, chi_circ_0013463, chi_circ_0000659, and chi_circ_0010484 were RYK , ESR1 , EVA1C, and SMAD5 , respectively. RTK is a member of the WNT signalling pathway receptor, and WNT has multiple biological functions and is highly correlated with female fertility ( Habara et al, 2021 ). The estrogen receptor alpha gene ( ESR1 ) is involved in hormonal regulation, whereas luteal phase OECs are predominantly secretory cells and are involved in estrogen secretion ( Abe, 1996 ), and estrogen is an important regulator of reproduction ( Oh et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%